รูปแบบความสัมพันธ์เชิงสาเหตุของปัจจัยวัฒนธรรมการทำงาน และปัจจัยคุณภาพชีวิตในการทำงานที่มีผลต่อ ความผูกพันของบุคลากรการไฟฟ้าส่วนภูมิภาค - ตาริชกุล วิไลพรรณ; พันธุ์ไทย เกรียงไกรยศ (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2017)
This research aimed to study the relationships between organizational culture, quality of work life and employee commitment of Provincial Electricity Authority and to study the direct and indirect influences of organizational culture, quality of work life on employee commitment of Provincial Electricity Authority and to investigate the causal relationship model between organizational culture and quality of work life on employee commitment of Provincial Electricity Authority. The research selected sample from Provincial Electricity Authority staff by Stratified Sampling for best sample and questionnaire was used as the tool for data collecting. The questionnaire was designed according to theory and operational definition.The statistics used in this research included, 1) Simple correlation analysis which was to investigate the relationships of organizational culture, quality of work life and employee commitment of Provincial Electricity Authority 2) Multiple regression which was to acquire the standard regression coefficient, path coefficient from the structure equation model in order to find out direct and indirect influences of independent variable towards dependent variable. The results were as follows: 1) Overall the independent variables that organization culture and quality of work life related to employee commitment of Provincial Electricity Authority under study were evinced at the statistically significant level of .05. 2) The independent variables had direct influences on employee commitment of Provincial Electricity Authority. The factors which influence the employee commitment are as follows; quality of work life in social relevance of work life, quality of work life in the total life space, mission culture and quality of work life in adequate and fair compensation. 3) Mission culture, Bureaucratic culture, Adaptability culture and Involvement culture that indirect influence on employee commitment of Provincial Electricity Authority in term of quality of work life in adequate and fair compensation, quality of work life in the total life space and quality of work life in social relevance of work life